2008
DOI: 10.1021/bi7020052
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Perturbed T1 Cu Sites in the Multicopper Oxidases Saccharomyces cerevisiae Fet3p and Rhus vernicifera Laccase:  Allosteric Coupling between the T1 and Trinuclear Cu Sites

Abstract: The multicopper oxidases catalyze the 4e- reduction of O2 to H2O coupled to the 1e- oxidation of 4 equiv of substrate. This activity requires four Cu atoms, including T1, T2, and coupled binuclear T3 sites. The T2 and T3 sites form a trinuclear cluster (TNC) where O2 is reduced. The T1 is coupled to the TNC through a T1-Cys-His-T3 electron transfer (ET) pathway. In this study the two T3 Cu coordinating His residues which lie in this pathway in Fet3 have been mutated, H483Q, H483C, H485Q, and H485C, to study ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 50 publications
8
51
0
1
Order By: Relevance
“…Still, it is clear that there is significant communication between the two redox sites in MCOs. These results are in accordance with the experimental observation that the redox potentials of Cu-T1 changes by up to 75 mV when two His ligands of the TNC were mutated [82].…”
Section: Reductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Still, it is clear that there is significant communication between the two redox sites in MCOs. These results are in accordance with the experimental observation that the redox potentials of Cu-T1 changes by up to 75 mV when two His ligands of the TNC were mutated [82].…”
Section: Reductionsupporting
confidence: 92%
“…Augustine et al [82] have investigated the influence of the mutation of the two His Cu-T3 ligands that lie along the Cu-T1 → Cu-T23 ET pathway to Gln and Cys residues. By using resonance Raman spectroscopy, they showed that these mutations increase the covalency of the Cu-S bond at the Cu-T1…”
Section: Electron-transfer Properties Of the Mcosmentioning
confidence: 99%
“…Laccases are generally found in plants and fungi [6], but they have also been reported in a few bacteria including Azospirillum lipoferum [7], Bacillus sphaericus [1], Marinomonas mediterranea [8] and Streptomyces griseus [9]. Although fungal laccases have a higher reduction potential of type I copper than bacterial laccases and this makes them more suitable for commercial applications [10] their use present the following drawbacks: slow growth and difficulty in controlling the glycosylation degree [11]. In addition, bacterial laccases are more amenable to genetic manipulation than fungal laccases [12].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In Nature the selective oxidation of lignin is carried out by white-rot basidiomycetes fungi that produce a pool of extracellular ligninolytic enzymes such as laccases and peroxidases. 5,6 In particular laccases can easily oxidise phenolic groups 7 and in presence of radical mediator, such as 1-hydroxybenzotriazole, their reactivity can be extended towards other functional groups as phenyl-aryl ethers. 8 Mn-peroxidase and lignin peroxidases are able to oxidize lignin at the phenolic and non-phenolic aryl-ether positions respectively.…”
Section: Introductionmentioning
confidence: 99%